Weighted a priori estimates for solution of (-Δ)mu = f with homogeneous dirichlet conditions - Duran, Ricardo Guillermo (2010)
Let u be a weak solution of (-Δ)mu = f with Dirichlet boundary conditions in a smooth bounded domain Ω ⊂ Rn. Then, the main goal of this paper is to prove the following a priori estimate: double pipeudouble pipeWω 2m,p(Ω) ≤ Cdouble pipefdouble pipeLω p(Ω), where ω is a weight in the Muckenhoupt class